Synthesis and physical studies of luminescent lanthanide and colorimetric chemosensors for ions and molecules - Leonard, Joseph (Trinity College (Dublin, Ireland). School of Chemistry, 2003)
This thesis, entitled "Synthesis and physical studies of luminescent lanthanide and colorimetric chemosensors for ions and molecules" is divided into six chapters. Chapter One, the introduction, includes a brief summary of what chemosensors are, specifically optical chemosensors. These are discussed in terms of the major components that make up chemosensors and the methods by which they work using relevant examples from the literature. Following this, a review on the use of lanthanide complexes as signalling moieties in optical chemosensing is presented. The design of lanthanide complexes with good optical properties is discussed, as is the mechanism by which lanthanide luminescence is produced.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin